Retrospective, real‐life study of venetoclax plus azacitidine or low‐dose cytarabine in French patients with acute myeloid leukemia ineligible for intensive chemotherapy. (8th December 2022) - Laloi, Louise; Billotey, Natacha Chaumard; Dumas, Pierre‐Yves; Paul, Franciane; Villate, Alban; Simand, Célestine; Fornecker, Luc; Puisset, Florent; Bertoli, Sarah; Simonet, Marion Boissard; Laribi, Kamel; Houyou, Dyhia; et al.
Abstract: Background: Recently, the combination of venetoclax plus a hypomethylating agent (HMA; azacitidine ordecitabine) or low‐dose cytarabine (LDAC) showed promise in Phase III trials in previously untreated AML. In France at the time of this study, venetoclax was not yet approved for AML and there were therefore no formal usage recommendations. Here we report the first study in a French cohort that assessed venetoclax in combination with existing treatments for AML under real‐life conditions. Method: This retrospective, real‐life study collected data on venetoclax use and management in a French cohort with acute myeloid leukemia (AML) ineligible for intensive chemotherapy. Result: Of 118 patients, 81 were in second line/beyond (71.6% also hypomethylating agent [HMA]; 23.5% lowdose cytarabine [LDAC]) and 37 in first line. For venetoclax initiation, 57.3% underwent ramp up and 74.6% were hospitalized. Median venetoclax duration was 2.5 months (range 0.03‐16.2). With all treatment lines and regimens, most common grade 3/4 adverse events were hematologic (overall 96.4% of patients) and infections (57.1%). Dosage adjustments for drug interactions and safety varied between centers. In second‐line/beyond, median progression‐free survival was 4.0 months (95% confidence interval [CI] 2.7‐12.8) with venetoclax‐HMA and 3.4 months (1.3‐8.9) with venetoclax‐LDAC; overall response rate was 51.9% and 41.2%, respectively. Thus, we showed that venetoclax‐based treatment yields promising findings in patients with AML, but to address treatment complexity, practice harmonization is needed. Abstract : Real life study of venetoclax treatment line and concomitant treatment with a hypomethylating agent (HMA)or low‐dose cytarabine (LDAC) in LAM. Venetoclax base treatment yields promising finding in AML patients ineligible to intensive chemotherapy. Practice harmonization could be future improvments.